Thin films of poly(vinylidene fluoride-co-hexafluoropropylene)-ionic liquid mixtures as amperometric gas sensing materials for oxygen and ammonia - Lee, Junqiao; Hussain, Ghulam; Lopez Salas, Nieves; MacFarlane, Douglas R.; Silvester, Debbie S. (The Analyst)
A gas sensor comprising of a planar electrode device covered with a thin layer of gel polymer electrolyte gave accurate and fast sensing responses for oxygen and ammonia detection in both the cathodic and anodic potential regions.
Keywords: Electrochemistry; Spectroscopy; Environmental Chemistry; Biochemistry; Analytical Chemistry

Modeling and Validating Fixed‐Bed Reactors: A State‐of‐the‐Art Review - Stegehake, Carolin; Riese, Julia; Grünewald, Marcus (ChemBioEng Reviews)
Abstract Modeling of heat and mass transfer in fixed‐bed reactors for heterogeneously catalyzed gas phase reactions is possible using different methods. Homogeneous and heterogeneous continuum models as well as particle resolved modeling of fixed‐bed reactors show high potential for application. Considering those approaches, advantages and disadvantages as well as underlying assumptions and boundary conditions are discussed. Additionally, methods for experimental validation are presented and discussed focusing on the two‐dimensional homogeneous models.
Keywords: Industrial and Manufacturing Engineering; Filtration and Separation; Process Chemistry and Technology; Biochemistry; Chemical Engineering (miscellaneous); Bioengineering

Encoding Metal–Cation Arrangements in Metal–Organic Frameworks for Programming the Composition of Electrocatalytically Active Multimetal Oxides - Castillo-Blas, Celia; Lopez Salas, Nieves; Gutiérrez, María C.; Puente-Orench, Inés; Gutiérrez-Puebla, Enrique; Ferrer, M. Luisa; Monge, M. Ángeles; Gándara, Felipe (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Improving Selectivity and Activity of CO2 Reduction Photocatalysts with Oxygen - Kreft, Stefanie; Schoch, Roland; Schneidewind, Jacob; Rabeah, Jabor; Kondratenko, Evgenii V.; Kondratenko, Vita A.; Junge, Henrik; Bauer, Matthias; Wohlrab, Sebastian; Beller, Matthias (Chem)
Keywords: Materials Chemistry; Biochemistry (medical); General Chemical Engineering; Environmental Chemistry; Biochemistry; General Chemistry

Metabolic Inflexibility Is an Early Marker of Bed-Rest–Induced Glucose Intolerance Even When Fat Mass Is Stable - Rudwill, Floriane; O’Gorman, Donal; Lefai, Etienne; Chery, Isabelle; Zahariev, Alexandre; Normand, Sylvie; Pagano, Allan F; Chopard, Angèle; Damiot, Anthony; Laurens, Claire; Hodson, Leanne; Canet-Soulas, Emmanuelle; et al. (The Journal of Clinical Endocrinology & Metabolism)
Abstract Context The effects of energy-balanced bed rest on metabolic flexibility have not been thoroughly examined. Objective We investigated the effects of 21 days of bed rest, with and without whey protein supplementation, on metabolic flexibility while maintaining energy balance. We hypothesized that protein supplementation mitigates metabolic inflexibility by preventing muscle atrophy. Design and Setting Randomized crossover longitudinal study conducted at the German Aerospace Center, Cologne, Germany. Participants and Interventions Ten healthy men were randomly assigned to dietary countermeasure or isocaloric control diet during a 21-day bed rest. Outcome Measures Before and at the end of the bed rest, metabolic flexibility was assessed during a meal test. Secondary outcomes were glucose tolerance by oral glucose tolerance test, body composition by dual energy X-ray absorptiometry, ectopic fat storage by magnetic resonance imaging, and inflammation and oxidative stress markers. Results Bed rest decreased the ability to switch from fat to carbohydrate oxidation when transitioning from fasted to fed states (i.e., metabolic inflexibility), antioxidant capacity, fat-free mass (FFM), and muscle insulin sensitivity along with greater fat deposition in muscle (P < 0.05 for all). Changes in fasting insulin and inflammation were not observed. However, glucose tolerance was reduced during acute overfeeding. Protein supplementation did not prevent FFM loss and metabolic alterations. Conclusions Physical inactivity triggers metabolic inflexibility, even when energy balance is maintained. Although reduced insulin sensitivity and increased fat deposition were observed at the muscle level, systemic glucose intolerance was detected only in response to a moderately high-fat meal. This finding supports the role of physical inactivity in metabolic inflexibility and suggests that metabolic inflexibility precedes systemic glucose intolerance.
Keywords: Biochemistry (medical); Clinical Biochemistry; Endocrinology; Biochemistry; Endocrinology; Diabetes and Metabolism

High-Q whispering gallery microdisk resonators based on silicon oxynitride - Hett, T.; Krämmer, S.; Hilleringmann, Ulrich; Kalt, H.; Zrenner, A. (Journal of Luminescence)
Keywords: Condensed Matter Physics; Biochemistry; General Chemistry; Atomic and Molecular Physics; and Optics; Biophysics

Cobalt-based nanocatalysts for green oxidation and hydrogenation processes - Jagadeesh, Rajenahally V; Stemmler, Tobias; Surkus, Annette-Enrica; Bauer, Matthias; Pohl, Marga-Martina; Radnik, Jörg; Junge, Kathrin; Junge, Henrik; Brückner, Angelika; Beller, Matthias (Nature Protocols)
Keywords: General Biochemistry; Genetics and Molecular Biology

Covalency of hydrogen bonds in liquid water can be probed by proton nuclear magnetic resonance experiments - Elgabarty, Hossam; Khaliullin, Rustam Z.; Kühne, Thomas D. (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Giant narrowband twin-beam generation along the pump-energy propagation direction - Pérez, Angela M.; Spasibko, Kirill Yu; Sharapova, Polina; Tikhonova, Olga V.; Leuchs, Gerd; Chekhova, Maria V. (Nature Communications)
Abstract Walk-off effects, originating from the difference between the group and phase velocities, limit the efficiency of nonlinear optical interactions. While transverse walk-off can be eliminated by proper medium engineering, longitudinal walk-off is harder to avoid. In particular, ultrafast twin-beam generation via pulsed parametric down-conversion and four-wave mixing is only possible in short crystals or fibres. Here we show that in high-gain parametric down-conversion, one can overcome the destructive role of both effects and even turn them into useful tools for shaping the emission. In our experiment, one of the twin beams is emitted along the pump Poynting vector or its group velocity matches that of the pump. The result is markedly enhanced generation of both twin beams, with the simultaneous narrowing of angular and frequency spectrum. The effect will enable efficient generation of ultrafast twin photons and beams in cavities, waveguides and whispering-gallery mode resonators.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef U.; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Silberhorn, Christine; Leuchs, Gerd; Marquardt, Christoph (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Alkaline Salts to Counteract Bone Resorption and Protein Wasting Induced by High Salt Intake: Results of a Randomized Controlled Trial - Bühlmeier, Judith; Frings-Meuthen, Petra; Remer, Thomas; Maser-Gluth, Christiane; Stehle, Peter; Biolo, Gianni; Heer, Martina (The Journal of Clinical Endocrinology & Metabolism)
Keywords: Biochemistry (medical); Clinical Biochemistry; Endocrinology; Biochemistry; Endocrinology; Diabetes and Metabolism

Paramagnetic Palladacycles with PdIIICenters Are Highly Active Catalysts for Asymmetric Aza-Claisen Rearrangements - Eitel, Simon H.; Bauer, Matthias; Schweinfurth, David; Deibel, Naina; Sarkar, Biprajit; Kelm, Harald; Krüger, Hans-Jörg; Frey, Wolfgang; Peters, René (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Assessment of serum levels of asymmetric dimethylarginine, symmetric dimethylarginine andl-arginine in coronary artery disease - Gad, Mohamed Z.; Hassanein, Sally I.; Abdel-Maksoud, Sahar M.; Shaban, Gamal M.; Abou-Aisha, Khaled; Elgabarty, Hossam (Biomarkers)
Keywords: Health; Toxicology and Mutagenesis; Clinical Biochemistry; Biochemistry

Biomimetic Synthesis of Resorcylate Natural Products Utilizing Late Stage Aromatization: Concise Total Syntheses of the Marine Antifungal Agents 15G256ι and 15G256β - Navarro, Ismael; Basset, Jean-François; Hebbe, Séverine; Major, Sarah M.; Werner, Thomas; Howsham, Catherine; Bräckow, Jan; Barrett, Anthony G. M. (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Trapping Metal-Organic Framework Nanocrystals: An in-Situ Time-Resolved Light Scattering Study on the Crystal Growth of MOF-5 in Solution - Hermes, Stephan; Witte, Thomas; Hikov, Todor; Zacher, Denise; Bahnmüller, Stefan; Langstein, Gerhard; Huber, Klaus; Fischer, Roland A. (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Controlled Formation of Ag Nanoparticles by Means of Long-Chain Sodium Polyacrylates in Dilute Solution - Huber, Klaus; Witte, Thomas; Hollmann, Jutta; Keuker-Baumann, Susanne (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Synthesis of a tin-functionalized cyclopentadiene derivative - Christoffers, Jens; Werner, Thomas; Baro, Angelika; Fischer, Peter (Journal of Organometallic Chemistry)
Keywords: Materials Chemistry; Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Biochemistry

Formation of Branched Calixarene AggregatesA Time-Resolved Static Light Scattering Study - Witte, Thomas; Decker, Björn; Mattay, Jochen; Huber, Klaus (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis